(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Covid-19 pandemic led to lockdown all parts of the world and, hence, changed some daily habits, including social interactions, the ability to perform sports, and— possibly— diet. The government of India established and promulgated lockdown policies on 19 March 2020. Nearly, 23.9% of responders did not substantially modify their diet during the lockdown; however, 76.1% of them reported that they changed their eating habit during lockdown, and 47.33% have gained their weight.. Nearly 41.66% of responders reported an increase in bread, chocolate, ice-cream, cakes, etc. Interestingly, 30.55% of responders increased their consumption of fresh fruit and vegetables in order to increase their immunity. Only 30.5% of those who declared decreased consumption attributed this change of diet to lower availability and ease of purchasing such items. Equally interesting, over 83.33% of responders, admitted that Aayurvaidik Kadha is very good in lockdown while 88.8% gives the preference to eat C vitamin content fruits.